INVESTIGATION OF GEOTHERMAL ENERGY RESOURCE POTENTIAL USING AERO-MAGNETIC AND AERO-RADIOMETRIC DATA OF KANO, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
This study focused on investigating the geothermal resource potential in Kano using high resolution aeromagnetic and radiometric data. A total of sixteen (16) sheets of aeromagnetic data with a block dimension of 55 km x 55 km were processed. Thus, the spectral centroid method which result from low wave number part of the wave number-scaled (depth to the centroid) and high-wave-number portion of the power spectrum (depth to the top) were estimated. Thus, the Curie point depth (CPD), geothermal gradient and heat flow were determined using appropriate parameters. The results showed that the CPD values range from 4.27 km to 19.59 km with an average of 11.83 km, and geothermal gradient ranges from 29.6 oC/km to 135.7 oC/m with an average of 82.7 oC/km while the heat flow ranges from 74 mW/m2 to 339.2 mW/m2 with the average of 206.6 mW/m2. Areas with high heat flow and shallow CPD could be prospective areas for geothermal energy. The values of the radiogenic heat obtained in the study area range from 0.15 to 2.77 Î¼W/m3. It was observed that the highest radiogenic heat generation in the area is greater than the average radiogenic heat values in the continental crust. The information obtained from temperature to depth model reveals that, the Curie temperature could be reached at the depths of 6 km within the regions.
Keywords: : Curie point depth, heat flow, geothermal gradient, radiogenic heat generation, temperature to depth variation.